Educação matemática e subjetivação em formas de vida da imigração alemã no Rio Grande do Sul no período da campanha de nacionalização - Junges, Débora de Lima Velho (Universidade do Vale do Rio dos Sinos, 2017)
The thesis aims to analyze how the school and, in particular, the school mathematics, operated as part of the process of subjectivation of students who was descendants of German immigrants in the estate of Rio Grande do Sul (far South of Brazil) during the happening of what was called “Campaign of Nationalization”. Specifically, identifies, in the talk of respondents, school rituals which operated as a tactic of manifestation of the truth that "the Germans are superior" and analyzes these rituals. Discusses also the rituals of school mathematics in which the tactics of the manifestation of truth operated by analyzing the mathematical language games that were present in these rituals, the way they were taught and that math skills were transmitted. The theoretical tools of the study are linked to the theorizing of Michel Foucault and Ludwig Wittgenstein. The research material consists of narrations of seven people who have studied in schools of German immigration in Rio Grande do Sul, in the period of the Campaign of Nationalization. The main results of the investigation indicate that the Deutschtum operated in the lives of German immigrants and their descendants, making them to perceive themselves above all as German settlers. Were identified three school rituals that operated in favour of the maintenance of Deutschtum and as a tactic for manifestation of the truth that the Germans were "superior individuals". About the mathematics, it was found that for the families of the participants of the survey it was important that his children dominate the rules and language games of the school mathematics to "honor" their German ancestry and preserve the Deutschtum. It was also possible to identify two rituals of school mathematics which operated as a way of strengthening the manifestation of the truth that the "Germans were superior." The first ritual was about making exercise in mathematic class and was noted that the lists of exercises were extensive and proposed questions that teachers expected/required that students apply the same grammatical rules and the same language games taught in the explanation and the examples presented, which were marked by the formalism and abstraction of school mathematics. Take ownership of the school mathematics language games was valued by both the teachers and the family, leading schoolchildren to consider that knowing the school mathematics was a necessary condition to be identified as "good Germans". The second rite of school mathematics focused on practice of realization of accounts considered "difficult". Those students that answered correctly, were placed as smart and examples to be followed; they were recognized as "real Germans", once mathematics were considered as a discipline of hard learning. These results provide elements that allow to infer that, in the form of life of German immigration in Rio Grande do Sul, during the period of the Campaign of Nationalization, was assumed to be a fact that the Germans were "superior individuals", being the school mathematics used to reinforce such manifestation.
Keywords: Processos de subjetivação; Rituais escolares; Matemática escolar; Imigração alemã; Campanha de nacionalização; Processes of subjectivation; School rituals; School mathematics; German immigration; Campaign of nationalization; ACCNPQ::Ciências Humanas::Educação